Organ Transplantation in Russia: An Anthropological Perspective - Mikhel, Dmitry (Anthropologica)

(untitled) (University of Victoria, 2021)
This article offers an anthropological perspective on organ transplantation in Russia. The author employs approaches and principles of medical anthropology and ontological turn in anthropology and attempts to present a novel human-object history of organ transplantation. This research focuses primarily on human collectives, such as medical communities and the rest of society, but also on certain objects, including donor organs and the infrastructure created by the technology. The article discusses the following questions: How does transplantation technology transform the medical community? How is it built into the social and cultural context? How is it perceived by the rest of society? How do some doctors try to adapt this technology to the traditional values of Russian society? This research was conducted at two large Russian organ transplantation centers. The analyzed materials include anthropological and medical publications, and mass media sources.